Respon Pemberian Bokhasi Kandang Sapi Dan Berbagai Mulsa Organik terhadap Pertumbuhan dan Produksi Tanaman Pare (Momordica Charantia L.) - Anna Millasarah Ritongga; Gusmeizal Gusmeizal; Erwin Pane (Universitas Medan Area, 2020)
Bitter melon is fast-growing favorable vegetable these days. Nevertheless, there is limited study about it. The study aims to determine the Response of Giving Bokhasi Cow Cages and Various Organic Mulch Against Growth and Production of Bitter Melon. The study was conducted at the University of Medan Area Experimental Garden on Jl. PBSI No.1 Medan Estate with a height of 23 meters above sea level. The design used in the study was a factorial Split Plot Design (RPT) consisting of 2 factors. The first factor is the provision of organic mulch which is placed as the main plot of 4 treatments, namely: M0: without mulch, M1: rice straw mulch, M2: alang-alang Mulch, M3: rice husk mulch and the second factor is the provision of cattle cages placed as a subplot of 4 treatments, namely: B0: without bokhasi cowshed, B1: bokhasi cowshed 10 tons/ha, B2: bokhasi cowshed 20 tons/ha, B3: bokhasi cowshed 30 tons/ha. This research with 3 replications. Observation parameters of plant height, number of leaves, fruit length, number of fruits, fruit wrap, sample weight, and plot weight. The results showed that: 1) Organic mulch administration significantly affected plant height observations with the best treatment of M1 (rice straw mulch). 2) Giving bokhasi cowshed significantly affected all parameters. 3) The results of the interaction analysis have a significant effect on observing the weight of the sample with the best treatment of M3B3 (rice husk mulch + bokhasi cattle cage 30 tons /ha).